Synergy Of Village-Owned Enterprises And Local Product-Based Umkm In Tourist Villages In Border Areas Indonesia - Timor Leste - Yohana Febiani Angi; Sarlin Paleina Nawa Pau (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The MSME sector is an economic milestone for villages in border areas. As one of the two countries' border crossings, tourist villages on the Indonesia-Timor Leste border have great potential in developing their business scale which can provide income not only for MSMEs, but for Border Village Original Income (PADes). However, the problem is that MSME actors in these border villages are still hampered in terms of capital, technological innovation, workforce expertise and marketing systems. On the other hand, the existence of Bumdes can be a solution to the problems faced by MSME actors. In this study, researchers will look for the root of the problems faced by MSMEs and BUMDes by conducting interviews with MSME actors, Village Heads and BumDes Management in 3 (Three) Border Villages, namely: Duarato Village, Tohe Village and Siwalan Village in Belu District. Then formulate policy priorities that must be implemented by the Village Government and BUMDes in order to move MSMEs through qualitative analysis techniques. The research results show that: (1) Business Environment Aspects; the importance of maintaining the surrounding environment so that it remains safe and conducive in supporting business development (2) Capital Aspects; access to capital from non-bank parties and from cooperatives to business actors (3) employment aspect; Local governments need to provide training facilities for workers. (4) Information Technology Aspects; every business actor has mastery of technology including mastery of banking digitization (5) Marketing Aspect; the importance of marketing training for business actors to maintain business continuity. The final implication of this research is the realization of BUMDes goals in driving the village economy. In addition, with the existence of the BUMDes program that supports MSMEs, it is hoped that it will be able to increase the business scale of MSMEs and Village Original Income (PADes) for tourist villages on the border of Indonesia - Timor Leste.